Toxoplasma GRA Peptide-Specific Serologic Fingerprints Discriminate Among Major Strains Causing Toxoplasmosis - Arranz-Solís, David; Carvalheiro, Cristina G.; Zhang, Elizabeth R.; Grigg, Michael E.; Saeij, Jeroen P. J. (Frontiers in Cellular and Infection Microbiology, 2021)
The severity of toxoplasmosis depends on a combination of host and parasite factors. Among them, the Toxoplasma strain causing the infection is an important determinant of the disease outcome. Type 2 strains dominate in Europe, whereas in North America type 2, followed by type 3 and 12 strains are commonly isolated from wildlife and patients. To identify the strain type a person is infected with, serological typing provides a promising alternative to the often risky and not always possible biopsy-based DNA methods of genotyping. However, despite recent advances in serotyping, improvements in the sensitivity and specificity are still needed, and it does not yet discriminate among the major Toxoplasma lineages infecting people. Moreover, since infections caused by non-1/2/3 strains have been associated with more severe disease, the ability to identify these is critical. In the present study we investigated the diagnostic potential of an ELISA-based assay using 28 immunogenic Toxoplasma peptides derived from a recent large-scale peptide array screen. Our results show that a discrete number of peptides, derived from Toxoplasma dense granule proteins (GRA3, GRA5, GRA6, and GRA7) was sufficient to discriminate among archetypal strains that infect mice and humans. The assay specifically relies on ratios that compare individual serum reactivities against GRA-specific polymorphic peptide variants in order to determine a “reactivity fingerprint” for each of the major strains. Importantly, nonarchetypal strains that possess a unique combination of alleles, different from types 1/2/3, showed either a non-reactive, or different combinatorial, mixed serum reactivity signature that was diagnostic in its own right, and that can be used to identify these strains. Of note, we identified a distinct “HG11/12” reactivity pattern using the GRA6 peptides that is able to distinguish HG11/12 from archetypal North American/European strain infections.